Impact of Third-Party Funds and Macroeconomic Variables on Micro, Small, and Medium Enterprises Financing by Islamic People's Financing Bank - Lestari, Lutfi Bangun; Achmad Nugrahantoro; Ilmi Masfuha; Ahmad Azhari Pohan; Gilang Mukti Prabowo (ITQAN: Journal of Islamic Economics, Management, and Finance, 2025)
This study aims to analyze the Impact of third-party funds and macroeconomic variables on MSME Financing by Islamic People's Financing Bank (BPRS) in Java: Evidence from the COVID-19 Period (2019–2023). The research method used is the GMM dynamic panel analysis approach. The object of the study is the BPRS located in Java for the period Q1 2019-Q42023. The sampling technique uses the saturated sampling technique. This study uses panel data from 98 BPRS in Java for Q12019-Q42023. This study found that DPK has a positive and significant effect, inflation has a positive but not significant effect, the benchmark interest rate has a negative but not significant effect, and COVID-19 has a significant negative impact on MSME financing. The results of this study provide empirical information that BPRS in Java has quite good resilience in dealing with economic instability due to the COVID-19 pandemic. The Islamic microfinance system has flexibility in dealing with crises. It contributes to fulfilling the objectives of Maqashid Sharia, especially in maintaining assets (high al-mal) and the sustainability of the community's economy.